Environmental risk assessment of the intake of contaminants in aquifers in the vicinity of a reclaimed waste dumpsite in Owerri municipal, Southeastern Nigeria - Francis Chizoruo Ibe; Alexander Iheanyichukwu Opara; Collins Emeka Amaobi; Bridget Onyekachi Ibe (Applied Water Science, 2021)
Abstract The study investigated groundwater sources within reclaimed municipal waste dumpsites around Akachi road in Owerri, Southeastern Nigeria. The research evaluated the pollution and risk inherent in the consumption of groundwater in the vicinity of the reclaimed waste dumpsite using standard procedures. Results showed acidic pH values for some groundwater samples within the reclaimed waste dumpsite. Elevated nitrate (NO3 −), aluminium (Al) and chromium (Cr) concentrations above the World Health Organization (WHO) limits for drinking water samples were recorded in some of the groundwater samples from the study area. The observed strong positive correlations between the metallic contaminants indicated that the distribution of the pollutants has a strong relationship with organic contaminants in the reclaimed waste dumpsite. Low contamination factor was exhibited by all metals for the individual samples except for Cr in sample A and Al in sample A and D. The pollution load index for all the samples was low, except for sample C with a pollution load index of unity. Elevated hazard quotient > 1 and hazard index > 1 were observed for both adults and children due to high Cr levels. The chronic daily intake risk assessment revealed values < 1, while carcinogenic risk values greater than 10−6 and 10−4 were observed for the samples suggesting potential health risk for children and adults. The water quality index of samples from the reclaimed waste dumpsite calls for concern due to elevated levels of Al and Cr. These findings, therefore, suggest the need to treat the groundwater from the reclaimed dumpsite before consumption to avert serious health risks. Finally, waste dumpsites should be remediated or allow to undergo natural remediation before reclamation, erecting residential structures, and sinking of boreholes for water supply within such areas.